Massive Cerebral Infarction Following Facial Injection of Autologous Fat: A Case Report and Review of the Literature - Qian, Huan; Ling, Yuxiao; Zhang, Mengwen; Lenahan, Cameron; Wang, Chen; Zheng, Zhe; Shao, Anwen; Zhang, Jianmin (Frontiers in Human Neuroscience, 2021)
Facial fat grafting techniques often offer impressive surgical results. However, fatal complications, such as irreversible cerebral ischemia, blindness, and hemiplegia are associated with them. We have presented a case report of a patient who presented with a massive cerebral infarction, a serious complication of facial autologous fat injection. The patient was a 28-year-old female who experienced motor dysfunction of the left extremities, which was accompanied with loss of consciousness immediately following fat grafting for facial augmentation. Imaging studies suggested that the patient had a large cerebral infarction on the right frontal, temporal, and parietal lobes due to complete occlusion of her right external carotid artery. Emergency decompressive craniectomy was completed in addition to multiple follow-up medical treatments. The patient recovered after four months with reduced motor function in her left upper extremity. This report further summarizes published cases of massive cerebral ischemia after facial injection of autologous fat, as well as lists high-risk facial areas and critical warnings.